MANAJEMEN STRATEGIK PENINGKATAN KINERJA DOSEN PERGURUAN TINGGI AGAMA ISLAM (Studi Kasus di UIN Malang) - Baharuddin, Mulyono (lp2m-uin malang, 2006)
The study is intended to investigate the design of strategic management to improve lecturer performance in Islamic Higher Education Institution (PTAI). Based on the data from the field research, UIN Malang has conducted strategic management to improve lecturer performance through improving the quantity and quality of lecturer performance. Strategic management user various approaches such as: (1) need analysis, (2) selection and recruitment, (3) pre-service training, (4) continuing the study, (5) the study, (6) religious teaching, (7) academic conference, (8) assistantship, (9) couching, (10) delegating job, (11) workshop, (12) teaching-learning activity, (13) research, (14) public service, (15) applied approach, (16) learning organization, (17) publishing journal, (18) mutual cooperation, (19) self improvement, (20) fellowship, (21) student control, (22) comparative study, (23) social weefare improvement, (24) regular advisory, and (25) regular meeting.Key words: Strategic management, Performance, PTAI.